Benutting van liturgiese ruimte in Pinksterkerke - Nel, Marius (HTS teologiese studies, 2015)
Utilisation of liturgical space in Pentecostal Churches. Afrikaans-speaking Pentecostal Churches were originally part of a revival movement that for various historical reasons chose not to be known as a church. The liturgical space in their churches reflected the anticlerical feeling. From the fifties of the previous century, however, it became important for Pentecostal Churches to be accepted as such within the community and the church world. This led to changes in the organisation of the liturgical space that began to duplicate the liturgical space of the three Afrikaans-speaking Sister churches to a large extent. From the nineties pulpits were replaced with a lectern, and the liturgical space adapted to reflect a new emphasis that became important for these churches. This article briefly examines the history of the use of liturgical space within Pentecostal Churches for the purpose of offering a theological reflection on current trends.